Prevalence of refractive error among Chinese preschool children: The Changsha children eye study - You, Yuxia; Fu, Junxia; Xu, Ming; Song, Yali; Zhou, Huanfen; Wei, Shihui (Frontiers in Public Health, 2022)
Purpose: We aimed to investigate the refractive status and prevalence of refractive error, and its characteristics in Chinese preschool children aged 1 to 6 years old. Methods: A population-based cross-sectional study Changsha Children Eye Study (CCES) was conducted. The prevalence of refractive errors among children aged one to six years old from 18 community health service centers was surveyed. A handheld child vision screener, Suowei, was used for examination. Results: A total of 43,105 preschool children were included. The mean spherical equivalent (SE) was 0.42 ± 1.05D for the right eyes. The mean astigmatism (diopter of cylinder, DC) was -0.83 ± 1.02D for the right eyes. The magnitude of refractive error was lower in older children, indicating the ongoing of the emmetropization during the 1-year-old to 6-year-old children. The prevalence of myopia (SE ≤-1.00D), hyperopia (SE ≥ +2.00D) and astigmatism (DC ≥1.50D) was 2.94%, 13.8% and 17.6%, respectively. The prevalence of myopia decreased with the increase of age between the six age groups (P＜0.001). The prevalence of hyperopia was lower in 5-6 years old, the prevalence of myopia was slightly higher at this period of time. With-the-rule (WTR) astigmatism (+ cylinder axis 90° ± 15°) was the most prevalent type of astigmatism than against-the-rule (ATR) astigmatism (+ cylinder axis 180° ± 15°) and oblique (OBL) astigmatism (X2 = 209.5, P＜0.001). The binary logistic regression model showed that older age and suffering astigmatism were independently associated with the development of myopia. In addition, there was no significant gender difference in the prevalence of myopia, emmetropia, and hyperopia. Conclusions: Our population-based cross-sectional study investigated the prevalence of myopia, hyperopia, and astigmatism in preschool children aged 1-6 years old. The distribution of the refractive error was disperse in the younger group and gradually turned more centralized in older group. Similar to hyperopia, with age increased, the prevalence of myopia was lower in preschool children younger than 5 years old and then slightly increased at 5 to 6 years, which may indicate an early sign of myopia in school-age children. Therefore, we emphasize that more attention should be given to children at this age.